PENGETAHUAN KESELAMATAN KERJA DAN STANDAR KUALITAS SERTA MATERIAL ALTERNATIF UNTUK MASYARAKAT INDUSTRI - Muhammad Najih; M. Fadhlan; Yoska Oktaviano; Yusep Mujalis; Sulamet-Ariobimo, Rianti Dewi (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
People's low knowledge of materials means that they can easily be confused or deceived by information about materials on social media or internet pages. Moreover, any information and/or news can be uploaded on social media or internet pages. So, the knowledge and competence of the author become biased and allow the public to receive information that is less or even incorrect which is then accepted as true. This can result in losses or even endanger the community. This Material Introduction and Characterization Training activity was held to help the community, especially the industrial community, to understand more about materials so that they can sort out the information they receive and apply the information correctly so that it will not harm themselves or their environment. This activity was well received by the community as seen from the number of participants who registered and then attended, as well as by looking at the number of participants who did not register but attended the activity. Participants gave good evaluations to the resource persons and hoped that this activity could be carried out more often.